PTU-012 Identifying differences in management of PBC to inform future practices -results from all-wales trainee collaborative. (June 2019) - Harborne, Philip; Shakespeare, Rachel; Haboubi, Hasan; Abdul-Sattar, Asma; Shenbagaraj, Lavanya; Navaratnam, Janardhan; Phillips, Andrew; Appanna, Gautham; Yahya, Imran; Edwards, Kate; Alrubaly, Laith; Newbould, Rachel; et al.
Abstract : Introduction: Primary biliary cholangitis (PBC) is a chronic autoimmune liver disease, which can progress to end-stage biliary cirrhosis. Risk stratification and assessment of response to treatment is important to target care and identify patients who may benefit from newer treatments to improve prognosis. We studied the clinical practice of patients with PBC across Wales, a geographically diverse region of over 3 million. Methods: A clinical audit tool was developed with UK-PBC and EASL guidelines. Data was retrospectively collected by specialist trainees in each health board. This included the use of ursodeoxycholic acid (UDCA), its appropriate dosing and assessment of response. The prevalence of cirrhosis and identification of high risk patients was also assessed. Results: A total of 406 patients with a diagnosis of PBC were identified across five Welsh health boards. Of these, the majority were female (73%). Mean age at diagnosis was 59.7 years (±13.5). Serological testing for PBC (AMA > 1/40) was present in 88.5% at time of diagnosis. Mean Alkaline Phosphatase (ALP) at diagnosis was 334U/L (56–2020). Mean follow-up since diagnosis was 7.9±6 years. Of 214 patients with recent clinic letters, 179 (83.6%) were on UDCA. Across health boards this ranged from 67.9% to 91.5%. Patients managed by hepatologists were more likely to be on the appropriate dose of UDCA (92.9%) compared to gastroenterologists (39.3%), p=0.018. Assessment of response to UDCA at 1 year was 59.3%. This was performed more frequently by hepatologists (86.8%) than gastroenterologists (62.5%), p=0.024. 47.8% of patients had cirrhosis. 18.4% of patients were identified as high risk as defined by a bilirubin >50umol/L or dropping albumin. Of 82 patients with clinic letters documenting a conversation about transplant, 26 patients were considered with 12 patients undergoing liver transplant. Conclusions: This study provides valuable insight into the care of PBC patients across Wales. It serves to highlight the wide variation and discrepancies in adherence to standards between hepatology and gastroenterology managed patients, despite widely available guidelines. In particular, patients managed by hepatologists were more likely to receive optimal UDCA dosing and have response documented at 1 year. This has important implications on accessing newer therapies. These findings will be used to review the PBC care pathway in Wales to improve adherence to standards and improve patient care